Feasibility of Pickling from Common Bean (Phaseolus vulgaris) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Common bean (Phaseolus vulgaris) is often a main source of protein, dietary fiber and minerals in diet offering benefits for human health. With the purpose of accelerating the commercial value of this vegetable, objective of this study focused on the lactic acid fermentation of the common bean into pickle. Different technical parameters such as blanching time and temperature, calcium chloride concentration in soaking, salt sugar percentage submersion affecting to fermentation were examined. This research was conducted in 2019 in the Labone Scientific laboratory. Results showed that 95oC in 6 seconds were suitable for blanching of common bean. The optimal calcium chloride concentration for soaking was recorded at 0.2% for soaking of common bean. The optimal salt: sugar was noticed at 7.5%:2.5% adequately for pickling in 14 days. As a result from pickling process, common bean will get a longer shelf life, translucent appearance, firm texture and pickle flavor. Pickled common bean was ideal for promoting the positive health image of probiotics. The findings of this investigation help diversifying the multiuse of common bean in food processing enterprises.Keywords: Common bean, Phaseolus vulgaris, Pickling, Blanching, Soaking, Calcium chloride.